2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-3.13515
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in pathogenesis of tumor growth and its possible application in cancer treatment

Abstract: Summary. In this review, the role of nitric oxide (NO) in the pathogenesis of the tumor growth and possibilities of its application in the treatment of cancer patients are analyzed. NO is one of the most important mediators of physiological processes being involved in the regulation of practically all body functions in health and disease. The role of NO in the development of many pathological conditions has been extensively studied and debated in recent years. Today it is clear that NO in relation to malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In addition, the clinical application of iNOS inhibitors for cancer therapy is controversial. Some studies have reported that the low level of iNOS is associated with a poor prognosis in CRC patients [160]; however, other studies have indicated a correlation between the low survival rates of patients and high level of iNOS in tumor tissues [54,161]. One study has even demonstrated that iNOS expression in tumors does not always correspond to the NO production level [162].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the clinical application of iNOS inhibitors for cancer therapy is controversial. Some studies have reported that the low level of iNOS is associated with a poor prognosis in CRC patients [160]; however, other studies have indicated a correlation between the low survival rates of patients and high level of iNOS in tumor tissues [54,161]. One study has even demonstrated that iNOS expression in tumors does not always correspond to the NO production level [162].…”
Section: Discussionmentioning
confidence: 99%
“…Once macrophages are recruited in the tumors, hypoxia-dependent transcription factors HIF1/2α reprograms macrophages into pro-tumoral phenotype that expresses IL-6, VEGF, and inducible nitric oxide synthase (iNOS) and arginase to promote tumor growth, angiogenesis, and immunosuppression ( 124 , 125 ). While iNOS is typically induced by M1 macrophages, studies have found that M2-like TAMs express iNOS at lower levels than M1 macrophages and these low levels of NO produced by TAMs inhibits tumor cell apoptosis and serves a cytoprotective function ( 126 128 ). Recent studies have shown that PTEN/PI3K/AKT signaling axis and Syk-Rac2 signaling axis promotes the stabilization of HIF1/2α in TAMs and polarization of macrophages into immunosuppressive phenotype in solid tumors ( 129 132 ).…”
Section: Tams In Neuroblastomamentioning
confidence: 99%
“…There is considerable evidence demonstrating a dual role of NO and S-nitrosylation in cancer risk and metastasis (Burke et al, 2017;Rizza and Filomeni, 2018;Ehrenfeld et al, 2019;Hays and Bonavida, 2019;Holotiuk et al, 2019;Somasundaram et al, 2019). The available evidence demonstrates a positive correlation between NO biosynthesis, tumor development and degree of malignancy in a variety of cancers (breast, pancreatic, liver, cervical, ovary, melanoma, nasopharyngeal, stomach, colon, lung, oral, esophagus, glioma, and prostate cancer) (Monteiro et al, 2015;Vanini et al, 2015;Burke et al, 2017;Thomas and Wink, 2017;Somasundaram et al, 2019).…”
Section: No and Tumor Cell Adhesionmentioning
confidence: 99%
“…On the other hand, when the endothelium is stimulated with pro-inflammatory agonist, the effects of NO have not been completely consistent. There is a vast body of evidence showing an inhibitory effect of NO on stimulated leukocyte adhesion (De Caterina et al, 1995;Liu et al, 1998;Baatz and Pleyer, 2001;Lelamali et al, 2001;Lo et al, 2001;Jiang et al, 2005;Shelton et al, 2008); while other reports demonstrate either no effect of inhibition of NO on leukocyte adhesion (Hickey et al, 2001;Shelton et al, 2008) or promotion -mediated by NO -of leukocyte adhesion in response to challenge with cytokines (Bessa et al, 2002;Joussen et al, 2002). These discrepancies may be due to several differences in experimental approaches including timing and duration of the application of agonist/antagonist.…”
mentioning
confidence: 99%